Perspectives of system informatics : 12th International Andrei P. Ershov Informatics Conference, PSI 2019, Novosibirsk, Russia, July 2-5, 2019, Revised Selected Papers /: 12th International Andrei P. Ershov Informatics Conference, PSI 2019, Novosibirsk, Russia, July 2-5, 2019, Revised Selected Papers. (2019) - Unknown
No abstract available